Pengaruh Konsentrasi Surfaktan Sodium Lauryl Sulfate (SLS) Terhadap Karakteristik Fisik Sediaan Facial Wash Minyak Biji Kelor (Moringa seed oil) - Sharon, Nela; Ibrahim, Nurlina; Sativa, Oriza (Herbal Medicine Journal, 2025)
Moringa seed oil contains high oleic acid, which can provide a moisturizing effect, so it can be used for making cosmetics, one of which is facial wash. Moringa seed oil facial wash can be used to cleanse facial skin from exposure to dust, pollution, dirt, and to moisturize the face. This study aimed to determine the effect and optimum concentration of sodium lauryl sulfate (SLS) on the physical characteristics of moringa seed oil facial wash preparations. The research method used was an experimental method. Facial wash was made in 3 formulas with the composition: F1: SLS 0.5%, F2: 0.75%, F3: 1%. The evaluations carried out included organoleptic, homogeneity, pH, viscosity, spreadability, foam stability and stability tests. The evaluation results of F1, F2 and F3 met the test parameters and were stable during storage. The conclusion of the study was that the higher the concentration of sodium lauryl sulfate (SLS), the higher the foam produced and the optimum formula of the facial wash preparation was F3 with an SLS concentration of 1%. According to the SNI 06-3532-1994 quality standard, the higher the foam produced, the better foam's stability.